Eligibility to Use the Fund's Facilities for Concessional Financing for 2017. (Policy Papers; Policy Paper ;, 2017)
The review of PRGT-eligibility, conducted biennially, is guided by a transparent, rules-based, and parsimonious framework. The framework determines which IMF members can access concessional resources based on an assessment of their level of income per capita, market access, and serious short-term vulnerabilities. Application of the framework should be consistent with the self-sustainability of the PRGT's lending capacity over time. This paper concludes that the existing framework remains generally appropriate. The PRGT-eligibility framework is broadly aligned with the World Bank's International Development Association practices, with minor differences between the lists of eligible countries explained by differences in the mandates of the two institutions and the timing of their respective review cycles. None of the countries that have graduated from the PRGT-eligibility list are at immediate risk of re-entering it. No country is proposed for graduation from or entry onto the PRGT-eligibility list. While thirteen countries meet either the income or market access graduation criterion, all are assessed to be facing serious short-term vulnerabilities and thus none are proposed for graduation. No non-PRGT-eligible country meets the criteria for entry onto the PRGT-eligibility list. The proposal to keep the list of PRGT-eligible countries unchanged is consistent with the self-sustained capacity of the PRGT.